Comparative effectiveness of lactulose and sennosides for the prevention of peritoneal dialysis-related peritonitis: an open-label, randomized, active-controlled trial. (1st January 2021) - Noppakun, Kajohnsak; Narongchai, Tichanun; Chaiwarith, Romanee; Wongsawad, Uraiwan; Vongsanim, Surachet; Ruengorn, Chidchanok; Nochaiwong, Surapon
Abstract: Background: To the best of our knowledge, the effectiveness and safety of lactulose in comparison to sennosides, for the prevention of peritoneal dialysis (PD)-related peritonitis, has never been tested in a randomized study. Methods: We conducted an open-label, randomized, active-controlled trial in a PD-center in Northern Thailand. Adult patients on PD were enrolled and randomly assigned in a 1:1 ratio into two groups; one group received lactulose 15 mL once daily ( n  = 50) and the other group received sennosides two tablets daily ( n  = 50). The primary outcome was time-to-first bacterial peritonitis. The secondary outcomes included a composite of bacterial peritonitis and all-cause mortality. Cox proportional hazards regression was calculated and presented as hazard ratios (HRs) with 95% confidence intervals (CIs). Results: One hundred PD patients were recruited (50.0% men; mean age 55.5 ± 13.0 years) in this study. The baseline characteristics of the study participants were similar in both groups. No significant trend towards a higher risk of PD-related peritonitis was observed in the lactulose group (HR, 2.32 [95% CI, 0.92–5.83]; p  = .051) compared to the sennosides group. Nevertheless, the secondary outcome was significantly higher in the lactulose group (HR, 2.77 [95% CI, 1.20–6.41]; p  = .010). The incidence of adverse events was not substantially different between the two groups; however, diarrhoea was more frequent in the lactulose group (38.0% vs. 18.0%; p  = .030) than in the sennosides group. Conclusions: Treatment with lactulose is not more effective than sennosides and cannot be routinely recommended for the prevention of peritonitis among the PD population. TRIAL REGISTRATION: Thai Clinical Trial Registry (clinicaltrials.in.th); ID: TCTR20171012001 KEY MESSAGE: To the best of our knowledge, no randomized controlled trial that compares the efficacy and safety profiles of lactulose versus sennosides for the prevention of PD-related peritonitis among the PD population has been conducted. In this open-label, randomized, active-controlled trial, treatment with lactulose is not more effective than sennosides in the prevention of PD-related peritonitis, and it could increase the risk of bacterial PD-related peritonitis. Further studies with a larger sample size by incorporated real-world evidence are needed to confirm our findings and to explore strategies to prevent peritonitis among PD patients.